The EU-Thailand Relations Tracing the Patterns of New Bilateralism - Kiatpongsan, Chaiyakorn (IIAS Publications Series, 2011)
This book focuses on the so-called 'new bilateralism' phenomenon, a foreign policy development that has widespread across regions since the mid-1990s. The book asks why the policy trend of 'new bilateralism' has been pursued in spite of the widely accepted views on political and economic advantages of 'multilateralism'. It also invites an open theoretical discussion on the implications of new bilateralism for international relations. Using the case study of EU-Thailand relations, the book shows that the opportunistic foreign policy behavior of the state is particularly observable in the crisis of multilateralism and that the prospects of bilateral engagement, identity formation and rhetorical action urge the drive to bilateralism with a high degree of pragmatism. This book offers important insight into how the new bilateralism operates, showing its advantages and disadvantages in the developing relationship between the EU and Thailand.